Allied health and nursing pre-registration student tracking studies: a scoping review protocol. (June 2018) - Khalil, Hanan; Sutton, Keith; Waller, Susan
Abstract : Review question: The objective of this scoping review is to examine the study designs and outcomes of allied health and nursing student and graduate tracking studies. Specifically the review questions are: What are the study designs of placement tracking studies for allied health and nursing students and graduates, as described in the literature? What are the outcomes reported in studies addressing allied health and nursing student and graduate tracking studies?